Mitochondrial heteroplasmy profiling in single human oocytes by next-generation sequencing. Issue 2 (2nd January 2017) - Ancora, Massimo; Orsini, Massimiliano; Colosimo, Alessia; Russo, Valentina; Marcacci, Maurilia; De Santo, Maria; D'Aurora, Marco; Stuppia, Liborio; Gatta, Valentina; Barboni, Barbara; Cammà, Cesare; Mattioli, Mauro
Abstract: Mitochondrial DNA (mtDNA) plays a key role in the development of a competent oocyte. Mutations of the mitochondrial genome lead to an altered energetic metabolism with negative effects on oocyte developmental competence. In this study, mtDNA heteroplasmy at an intra-oocyte level and between the different analyzed human oocytes ( n  = 12) was identified by a next-generation sequencing (NGS) protocol previously developed by this research group and submitted to GenBank. This method highlighted, in particular, variants in the genes involved in the respiratory chain providing a direct indication of the cell-specific damage within the mitochondrial genome as predictor of the oocyte quality.